Ertapenem Articulating Spacer for the Treatment of Polymicrobial Total Knee Arthroplasty Infection - Dragan Radoicic; Milomir Milanovic; Jugoslav Marinkovic; Danica Radoicic (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Periprosthetic joint infections (PJIs) are the primary cause of early failure of the total knee arthroplasty (TKA). Polymicrobial TKA infections are often associated with a higher risk of treatment failure. The aim of the study was to assess the efficacy of ertapenem loaded spacers in the treatment of polymicrobial PJI. Methods. There were 18 patients enrolled; nine patients with polymicrobial PJI treated with ertapenem loaded articulating spacers were compared to the group of 9 patients treated with vancomycin or ceftazidime loaded spacers. Results. Successful reimplantation with revision implants was possible in 66.67%. Ertapenem spacers were used in 6 cases in primary two-stage procedure and in 3 cases in secondary spacer exchange. Successful infection eradication was achieved in all cases; final reimplantation with revision knee arthroplasty implants was possible in 6 cases. Conclusion. Ertapenem can be successfully used as antimicrobial addition to the cement spacers in two-stage revision treatment of polymicrobial PJIs. However, this type of spacer may also be useful in the treatment of infections caused by monomicrobial extended spectrum beta-lactamases producing gram-negative bacilli. Further clinical studies are required to evaluate the efficacy and safety of ertapenem spacers in the treatment of polymicrobial and monomicrobial PJIs.